Implementing differentiated education: why diversity must be appreciated (2017)
This reflection paper illustrates the relevance of differentiated education in our current times, which brings to light students’ learning differences and innovative tailored-teaching approaches, leaving behind the traditional so called onesize-fits-all teaching method. The author will start by defining what differentiation is about. She will proceed by explaining the advantages of implementing differentiated education in our classrooms at all ages and subjects as well as describing potential activities to promote flexible-customized lessons based on students’ needs and varied academic performance levels. The author will end describing a set of strategies to target students’ senses, encourage problem-solving skills, support cooperative learning, and adapt assignments so learners feel capable of succeeding in an academic setting.